TANGGUNG JAWAB MASKAPAI PENERBANGAN PERINTIS TERHADAP KERUGIAN ATAS MUSNAHNYA KARGO AKIBAT KECELAKAAN - Celfilia Devi Ayuningtyas (Program Studi Hukum Universitas Sulawesi Barat, 2023)
The existence of pioneering cargo air transportation is an important aspect of people’s need who live in 3T (undeveloped, isolated, and outermost) areas of Indonesia. The main function of pioneering air transportation is to minimize price disparities which are very detrimental to the people of 3T area. However, in practice, the operation of pioneering cargo air transport, encountered various obstacles that resulted in aviation accidents which became the most accidental cases compared to commercial flights. So based on these problems, this research is intended to examine the legal position of pioneering cargo air transportation in Indonesia to further determine the responsibility of pioneer airlines for aviation safety and the losses incurred for the destruction of cargo in the event of an accident. The research method used in this research is normative juridical through a study of concepts and related regulations. The results of the study indicate that the legal position of pioneering cargo carriers is not only as a carrier in a cargo transport agreement but also has a legal relationship with the government based on a contract as part of the implementation of public services. Pioneer airlines are responsible together with local governments, airport authorities, and related parties to ensure flight safety as a preventive measure for accidents. If there has been an accident that destroyed the cargo, the airline is responsible for fulfilling the compensation suffered by the sender in nominal terms based on the provisions of the applicable air transportation regulations.